Management of penetrating abdominal trauma in a resource limited setting of a district medical college, during COVID-19 pandemic: a case report - Bharti, Ramesh; Bhatia, Arvind; Dutt, Sunil; Taneja, Parvez; Sood, Saloni; Chaudhary, Rajesh (International Surgery Journal, 2022)
Penetrating trauma abdomen is a leading cause of injuries in the modern times. Most common causes are stabbing, gunshot wounds and industrial accidents. We present a case of penetrating trauma abdomen caused by a small metallic foreign body which entered through the anterior abdomen wall, caused jejunal perforation below umbilicus and was found in the lesser sac. It was a management challenge as we are a resource limited, newly established district medical college where the next referral centre is nearly 150 km away. The patient underwent a successful laparotomy where the perforation of the intestine was closed primarily and the foreign body was retrieved.